THE PROBLEMS OF INFORMATION DEFENCE IN DIAGNOSIS INTELLIGENT SYSTEMS OF MICROPROCESSOR DEVICES - Lokazyuk, Viktor; Pomorova, Oksana (International Journal of Computing, 2014)
The method for protection of diagnosis intelligent system of microprocessor devices is represented in the paper. This method based on background authentication of the user in the process of keyboarding. The user’s keystroke dynamics characteristics are the means of authentication. For realization of the user authentication method uses the artificial neural networks of ART2 architecture.